Quality Characteristics Of Quail Meatballs - Ikhlas, Boni (2011)
Quail is one of the important sources of poultry meat besides chicken, but its usefulness for the production of meat products has not been popular. Nutritional and physicochemical analyses of young and spent of quail were conducted in this study. The study also evaluated the chemical, physicochemical, and sensory characteristics of quail meatballs prepared using different types of flour as a binder (cassava, corn, wheat, sago, and potato flour). Extracts from Cosmos caudatus (ulam raja) and Polygonum minus (kesum), and synthetic antioxidant Butylated Hydroxy Toluena (BHT) were added to quail meatballs formulation and stored for 21 days.